Wiskott Aldrich Syndrome - Şenay Yapıcı; S. Şebnem Kılıç (Güncel Pediatri)
The Wiskott Aldrich Syndrome (WAS) is a well defined X-linked recessive disorder associated with microplatelet thrombocytopeniae, eczema, secondary pyogenic infections, and an increased risk of autoimmunity and lymphoreticular neoplasia. The responsible mutations that are associated with WAS and X-linked thrombocytopeniae are mutations in the WAS protein. Severity of the disease varies with types of WASP mutations. Hematopoietic stem cell transplantations or gene therapy is the only curative therapy for WAS patients. Improved profilactic antimicrobial therapy againts secondary infections and prophylactic use of IVIG have markedly prolonged the life expectancy of WAS patients. (Journal of Current Pediatrics 2008; 6: 119-23)